Impacts of brand image on customer awareness and sales: A case study of Vodacom Arusha branch - Kaaya, Enedy Victor (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the degree of Masters of Business Administration in Corporate Management (MBA-CM) of Mzumbe University